An assessment of revenue mobilisation trends in metropolitan, municipal and district assemblies: the case of La Dade-Kotopon Municipal Assembly. - Salam, Haruna Abdul (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Award Of The Degree Of Master Of Business Administration (Strategic Management Option).